Activity and Well-Being of Older Adults: Does Cognitive Impairment Play a Role?. (March 2014) - Johnson, Justin D.; Whitlatch, Carol J.; Menne, Heather L.
This analysis assesses the activity level of 324 older adults and the relationship of activity to quality of life with a specific emphasis on the role of cognitive ability. Although the number of older adults with cognitive impairment continues to grow, few studies have examined the variation in activity and quality of life based on the older adults' cognitive status. Results indicated that cognitively impaired older adults were less active than their nonimpaired peers; however, correlations revealed that regardless of impairment status, more activity was related to a higher quality of life. There was no support for the hypothesis that impaired older adults who have more cognitive ability will have a higher rated quality of life. These results should be considered in the development of programs for older adults. Regardless of impairment level, activity is paramount to maintaining quality of life.